SUSTAINABLE FINANCE: EVALUATING THE ROLE OF GREEN BONDS IN GLOBAL CAPITAL MARKETS - Posumah, Nurcahya Hartaty (Management Studies and Business Journal (PRODUCTIVITY), 2025)
In recent decades, green bonds have emerged as a significant financial instrument in supporting sustainable finance and facilitating environmentally friendly investments. This research aims to evaluate the contribution of green bonds to the development of sustainable finance in the global capital market. Through a Systematic Literature Review (SLR) approach, we analyze various empirical studies and relevant industry reports. Findings show that green bonds not only increase access to funding for renewable energy and sustainable infrastructure projects, but also provide financial benefits through transparency and market stability. However, challenges such as greenwashing risks and lack of consistent certification standards still hinder the growth of this market. This research provides insights for investors, policy makers and academics in formulating more effective strategies to support the transition to a green economy.